PENERAPAN MODEL PEMBELAJARAN SELF ORGANIZED LEARNING ENVIRONMENTS (SOLE) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA KELAS VII-2AN KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA KELAS VII-2 - Simamora, Joice Ronitua; Yuni Rhamayani; Nova Christina Dewi (Yayasan Perguruan Kampus, 2025)
This type of research is Classroom Action Research which aims to improve students' critical thinking skills in mathematics through the Self Organized Learning Environments (SOLE) learning model. The subjects in this study were students of class VII 2 SMP Negeri 5 Padangsidimpuan. The object in this study is the application of the Self Organized Learning Environments (SOLE) learning model to improve the critical thinking ability of mathematics students in class VII 2 of SMP Negeri 5 Padangsidimpuan in the 2023/2024 academic year. In terms of the level of students' mathematical critical thinking ability, after the implementation of PTK actions, it can be seen from the students' mathematical critical thinking ability test with a percentage of assessment in cycle I 66.67% with the category “Fair” and the percentage of cycle II assessment 85.18% with the category “Good”. Based on the observation of student activity in cycle I, it was obtained that the level of student activity was 67.42% in the “Fair” category and in cycle II there was an increase in student activity to 83.91% in the “Good” category. The conclusions in this study are (1) the use of the Self Organized Learning Environments (SOLE) learning model can improve students' critical thinking skills in mathematics on the material of triangular flat shapes in class VII-2; (2) The use of the Self Organized Learning Environments (SOLE) learning model can increase student activity on the material of triangular flat shapes in class VII-2.